Actual and undiagnosed HIV prevalence in a community sample of men who have sex with men in Auckland, New Zealand - Saxton Peter JW; Dickson Nigel P; Griffiths Richard; Hughes Anthony J; Rowden John (BMC, 2012)
Abstract Background The prevalence of HIV infection and how this varies between subgroups is a fundamental indicator of epidemic control. While there has been a rise in the number of HIV diagnoses among men who have sex with men (MSM) in New Zealand over the last decade, the actual prevalence of HIV and the proportion undiagnosed is not known. We measured these outcomes in a community sample of MSM in Auckland, New Zealand. Methods The study was embedded in an established behavioural surveillance programme. MSM attending a gay community fair day, gay bars and sex-on-site venues during 1 week in February 2011 who agreed to complete a questionnaire were invited to provide an anonymous oral fluid specimen for analysis of HIV antibodies. From the 1304 eligible respondents (acceptance rate 48.5%), 1049 provided a matched specimen (provision rate 80.4%). Results HIV prevalence was 6.5% (95% CI: 5.1-8.1). After adjusting for age, ethnicity and recruitment site, HIV positivity was significantly elevated among respondents who were aged 30-44 or 45 and over, were resident outside New Zealand, had 6-20 or more than 20 recent sexual partners, had engaged in unprotected anal intercourse with a casual partner, had had sex with a man met online, or had injected drugs in the 6 months prior to survey. One fifth (20.9%) of HIV infected men were undiagnosed; 1.3% of the total sample. Although HIV prevalence did not differ by ethnicity, HIV infected non-European respondents were more likely to be undiagnosed. Most of the small number of undiagnosed respondents had tested for HIV previously, and the majority believed themselves to be either "definitely" or "probably" uninfected. There was evidence of continuing risk practices among some of those with known HIV infection. Conclusions This is the first estimate of actual and undiagnosed HIV infection among a community sample of gay men in New Zealand. While relatively low compared to other countries with mature epidemics, HIV prevalence was elevated in subgroups of MSM based on behaviour, and diagnosis rates varied by ethnicity. Prevention should focus on raising condom use and earlier diagnosis among those most at risk, and encouraging safe behaviour after diagnosis.